2005
DOI: 10.1021/cm051935n
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Mesoporous Organosilicas with a Bifunctional Conjugated Organic Unit and Crystal-like Pore Walls

Abstract: The synthesis of a 2D hexagonal highly ordered periodic mesoporous 1,4-divinylbenzene-bridged organosilica (PMO) with crystal-like pore walls is reported. Both functionalities are realized by utilization of one single precursor (1,4-bis-((E)-2-(triethoxysilyl)vinyl)benzene (BTEVB) which was synthesized via Pd-catalyzed double Heck coupling of 1,4-dibromobenzene with vinyltriethoxysilane. Solid state 29Si MAS NMR and FT-IR spectroscopy confirms that during the hydrothermal PMO synthesis and subsequent extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 16 publications
2
73
1
1
Order By: Relevance
“…[4][5][6] Most of these materials have amorphous pore wall structures, that is, the organic groups are randomly arranged within the framework. In a few selected cases [R = C 6 H 4 , [7][8][9][10] (C 6 H 4 ) 2 , [11,12] CH=CH, [7,13,14] CH=CH À C 6 H 4 À CH= CH, [15,16] and 2,6-naphthylene [17] ), the self-organization of bis-silylated organic precursors has been exploited to prepare PMOs with molecular scale ordering of the organic groups within the pore walls. [18,19] The first report of an ordered mesoporous material possessing a crystal-like periodic pore wall structure came from Inagaki et al, who used 1,4-bis(triethoxysilyl)benzene (BTEB) as the precursor to a phenylene-silica hybrid mesoporous material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Most of these materials have amorphous pore wall structures, that is, the organic groups are randomly arranged within the framework. In a few selected cases [R = C 6 H 4 , [7][8][9][10] (C 6 H 4 ) 2 , [11,12] CH=CH, [7,13,14] CH=CH À C 6 H 4 À CH= CH, [15,16] and 2,6-naphthylene [17] ), the self-organization of bis-silylated organic precursors has been exploited to prepare PMOs with molecular scale ordering of the organic groups within the pore walls. [18,19] The first report of an ordered mesoporous material possessing a crystal-like periodic pore wall structure came from Inagaki et al, who used 1,4-bis(triethoxysilyl)benzene (BTEB) as the precursor to a phenylene-silica hybrid mesoporous material.…”
Section: Introductionmentioning
confidence: 99%
“…Bromination experiments performed for vinylene-and phenylenedivinylene-bridged PMOs showed that up to 35% of the organic groups were accessible for functionalization. [14,16] Crystal-like mesoporous phenylene-silica can be sulfonated in one step (by treatment with fuming sulfuric acid or chlorosulfonic acid) or aminated in two steps (by nitration with HNO 3 -H 2 SO 4 followed by treatment with SnCl 2 -HCl). [7,22,23] The amino-functionalized material was found to be a reusable base catalyst for the Knçevenagel condensation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The organic functionality of PMO materials can be tuned to suit the application required. For example, Cornelius et al [33] synthesized a PMO using 1,4-bis((E)-2-(triethoxysilyl)vinyl) benzene to introduce two organic functionalities into the pore wall structure, a vinyl group and an aromatic ring. These groups can be further functionalised if required.…”
Section: Bridged Silesquioxanesmentioning
confidence: 99%
“…There are enormous possibilities to deliberately tune the chemical and physical properties of the PMOs by varying the organic spacer groups of the organosilica precursors, which makes these materials interesting for applications such as catalysis, adsorption, chromatography, or host-guest chemistry. [4,5] The organic bridging groups of the organosilica precursors that have been successfully converted into PMO materials include, for instance, methylene, [6] ethylene, [1,3] ethenylene, [2,3] phenylene, [7] biphenylene, [8] thiophene, [7,9] and divinylphenylene [10,11] units. It was also possible to prepare PMOs possessing molecularscale periodicity inside the channel walls instead of the common observed amorphous pore walls as a result of a highly cooperative process.…”
Section: Introductionmentioning
confidence: 99%